MENYELARASKAN PEMBERDAYAAN BANK SAMPAH BERBASIS TEKNOLOGI DENGAN MANAJEMEN BISNIS SYARIAH DI DESA CIBITUNG WETAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR. - Mugi Komara Baibars; Tubagus Rifqy Thantawi; Bayu Purnama Putra (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2021)
Abstract The introduction of a waste bank in Cibitung Wetan Village, Bogor Regency, West Java has been socialized in 2021. This is based on the accumulation of garbage in the village due to the public's reluctance to spend money every month for transporting waste from the cleaning service. The existence of this activity in community empowerment is to strengthen the management of the Waste Bank 'Seroja Kahuripan' so that it has a clearer structure and division of labor, the number of waste bank customers has increased to 57 people, the post for weighing the waste bank with various supporting tools and additional income of around >200,000 -300,000/year/person. The improvement in the skills of waste bank members is felt through various trainings that have been carried out such as: sorting organic and inorganic waste, training on inorganic waste management, especially the use of glass bottles and plastic crackers, training in making processed product packaging, utilizing organic waste by planting nutritious vegetable gardens and managing waste banks. manually and digitized via software. The use of technology as a result of downstream research through computerized waste bank applications makes it easier to carry out waste bank administration which is routinely carried out every two weeks. The results of the partner satisfaction questionnaire show that waste bank respondents are very satisfied with this application because it can help with various obstacles ranging from the transaction recording process, weighing waste, errors in inputting data from weighing results to avoiding suspicion between officers and customer. Keywords : Waste Bank, Technology, Village Empowerment